Economic Impact of Involuntary Resettlement Programmes in Sri Lanka A Study of Lunawa Environmental Improvement and Community Development Project - Udayangani, K.P.I. (University of Sri Jayewardenepura Nugegoda, 2011)
The primary goal of an involuntary resettlement process is to prevent poverty and to improve the livelihood of resettlers. To do this government and implementing agencies must understand the economics of dispossession, poverty and recovery, and plan for growth at the relocation site. Development intervention such as a road or canal development project should proceed for the greater benefit of society, in spite of its potential adverse effects on some people. In such cases, the people who may be adversely affected by the development intervention should be consulted, compensated for their losses, and assisted to rebuild their homes and communities, re-establish their enterprises, and develop their potentials as productive members of society at a level generally at least equivalent to that which was likely to have prevailed in the absence of the development intervention. The development of Lunawa Environmental Improvement and Community Development Project implied many benefits besides canal development, for example alleviating flood, creating a hygienic and pleasant environment, upgrading living conditions of the communities. The project involved impacts such as involuntary resettlement of nearly 1900 people living at the canal bank. The aim of this dissertation is to study whether there is a positive economic impact on project affected persons due to the implementation of the Lunawa Environmental Improvement and Community Development Project. Specifically, the dissertation examines the best alternatives to resettle project affected people, process applied in the resettlement programme, compensation process, issues associated with the resettlement programme and to suggest a better policy framework for resettlement. Stratified sampling method was carried out to select the sample and total of 300 project affected people were selected accordingly. The sample was subjected to a questionnaire survey and responses were analyzed to identify the economic impact on the basis of before and after the project using SPSS tool. Further, a Composite Index exclusively applicable to this resettlement programme was formulated and it revealed that, economic, physical, and social factors were positively affected by the project. Such positive effects on economic, physical, and social factors indicate that the benefits of the project have flowed down to the affected parties. In addition, relocation of affected parties' Off—Site was identified as the best method for resettlement.